Clinical image-based procedures : translational research in medical imaging : 4th International Workshop, CLIP 2015, held in conjunction with MICCAI 2015, Munich, Germany, October 5, 2015. Revised Selected Papers /: translational research in medical imaging : 4th International Workshop, CLIP 2015, held in conjunction with MICCAI 2015, Munich, Germany, October 5, 2015. Revised Selected Papers. (2016) - Unknown
No abstract available